Etica, diritto e design tecnologico: un modello per la “Legge sull’Intelligenza Artificiale” - Costantini, Federico (Teoria e Critica della Regolazione Sociale / Theory and Criticism of Social Regulation, 2022)
This contribution outlines the background in which the recent Proposal for a Regulation (EU) “Artificial Intelligence Law” adopted by the European Parliament on 21 April 2021 is set. After few preliminary historical notes on the reception of cybernetics in Italy, the relationship between law and information technology is framed through an ideal three-tiered path with the aim of explaining how the central role of law is played today by technological design and how its three traditional conjugations – justice, validity, effectiveness – can be reconfigured today as variants of the notion of “information”. In conclusion, some overall considerations are given, and future research paths are identified.